Evaluating the Cumulative Effects of Livestock Grazing on Wildlife With an Integrated Population Model - Milligan, Megan C.; McNew, Lance B. (Frontiers in Ecology and Evolution, 2022)
Livestock grazing can shape temperate grassland ecosystems, with both positive and negative effects on wildlife documented depending on a variety of grazing and site factors. Historically, research investigating the impacts of livestock grazing on wildlife has been limited by a narrow focus on simple ‘grazed’ versus ‘ungrazed’ treatments or examining how grazing affects only a single vital rate in isolation. To overcome these limitations, we used a two-stage class, female-based integrated population model (IPM) to examine whether three grazing management regimes (season-long, rest-rotation, and summer rotation) differentially impacted population growth rates of sharp-tailed grouse (Tympanachus phasianellus) in eastern Montana and western North Dakota. We estimated 14 vital rates related to survival and fecundity and examined whether subtle cumulative effects of livestock grazing were present but not detected in prior analyses focused on single vital rates. While the management regimes did not differentially impact survival or fecundity of female grouse in our study system, we found evidence for significant cumulative impacts of grazing regime on population growth rates that were only apparent when all vital rates were evaluated concurrently. Population growth rates were higher in areas managed with season-long livestock grazing. The IPM framework encourages comprehensive investigations into the influence of covariates on critical components of species life histories and can assist in guiding management decisions in a world of limited resources. This integrated approach allowed us to more efficiently use multiple data types to provide a more complete picture of the effects of management on an important indicator species.